2020
DOI: 10.3390/su12062457
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Socio-Economic Factors on Sediment Load: A Case Study of the Yanhe River Watershed

Abstract: Under the influence of climate change and human activities, sediment load in rivers has changed significantly, which has a profound impact on the stability of ecosystems and the sustainable development of human beings. Taking the Yanhe River watershed as a case, this paper expounds the dynamic relationship among the Grain for Green Project, social and economic development, population migration, and sediment transport. The variability of sediment load was detected by Pettitt test, the double cumulative curve me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(23 citation statements)
references
References 64 publications
(69 reference statements)
1
10
0
Order By: Relevance
“…Human activities in the basin were directly responsible for 89% of reduction in sediment load. These results are consistent with previous research, which has indicated the dominance of human impact on sediment reduction in rivers [52][53][54][55][66][67][68][69][70]. The effect of urbanization in modern conditions is absorbed by even the most remote villages and, thus, an increasing amount of rural population accepts the values of urban areas [34].…”
Section: Long-term Trend and Change-point Analysessupporting
confidence: 92%
See 2 more Smart Citations
“…Human activities in the basin were directly responsible for 89% of reduction in sediment load. These results are consistent with previous research, which has indicated the dominance of human impact on sediment reduction in rivers [52][53][54][55][66][67][68][69][70]. The effect of urbanization in modern conditions is absorbed by even the most remote villages and, thus, an increasing amount of rural population accepts the values of urban areas [34].…”
Section: Long-term Trend and Change-point Analysessupporting
confidence: 92%
“…The method uses linear regression analysis of cumulative precipitation, water discharge, and suspended sediment load time-series data. The application of this method has been described in many studies [51][52][53][54][55]. In this study, identifying the baseline period was one of the most important steps in the process.…”
Section: Double-mass Curve Methods and Linear Regression Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Irrigation is an important aspect of water resource management in inland river basins, and is critical to policy formulation in the agriculture sector. Water security in arid regions is extremely sensitive to climate change and increasing human activities (Timpane et al, 2017;Waseem et al, 2020;Zhong et al, 2020). It is closely tied to knowledge of the existing available water resources and the spatial-temporal variations of water demand from different water users (Masafu et al, 2016;Deng and Chen, 2017;Luo et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…In recent decades, the impact of climate change and human activities on the global environment has become more and more obvious. In particular, it has affected the spatial and temporal distribution of surface water resources and various factors in the water cycle (runoff and sediment load) [2].…”
Section: Introductionmentioning
confidence: 99%